An Analysis on Textbook Material Entitled “5 Langkah Jitu Membaca Kitab Gundul” Written by Abdul Haris - Muhammad Farhan Azizi; Ahmad Fatoni (Al-Kalimat: Journal of Linguistic and Arabic Teaching, 2026)
In reading Kitab Gundul (Turāts), Arabic grammar learning tends to be theoretical, recitation-centered, and time-consuming. Solving these problems requires selecting and arranging the textbook used as the learning media. The textbook “5 Langkah Jitu Membaca Kitab Gundul” by Abdul Haris offers solutions to those problems. Therefore, this study analyzed the selection and gradation of the book. The approach applied in this study is a qualitative method of conducting library research. The result of the study explains that the book refers to the appropriate selection principles, which include the learning objective (being able to read Arabic texts both in class or individually), the need of the target group, learning duration, language simplification, and the solution-offer called 234 (Dji Sam Soe) technique as the additional factor. Additionally, its gradation factor is based on grammatical categories. At the same time, the selection started with word concept, followed by sentence concept, and finally, sentence structure analysis using the 234 (Dji Sam Soe) technique.